2018
DOI: 10.1016/j.ijcard.2017.10.064
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes in adults with congenital heart disease: Inter-country variation, standard of living and healthcare system factors

Abstract: This international collaboration allowed us to determine that PROs in ConHD vary as a function of patient-related factors as well as the countries in which patients live.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 27 publications
5
75
2
Order By: Relevance
“…These factors explained 20% of the variance of QoL, indicating that there was still a large portion of the variance that could not be explained. APPROACH‐IS reported that sex, educational level and the complexity of the heart defect were not associated with QoL . The finding that disease complexity did not play a role in predicting QoL could be explained by the fact that we measured QoL from a holistic point of view, instead of a merely functional perspective.…”
Section: Approach‐ismentioning
confidence: 90%
See 3 more Smart Citations
“…These factors explained 20% of the variance of QoL, indicating that there was still a large portion of the variance that could not be explained. APPROACH‐IS reported that sex, educational level and the complexity of the heart defect were not associated with QoL . The finding that disease complexity did not play a role in predicting QoL could be explained by the fact that we measured QoL from a holistic point of view, instead of a merely functional perspective.…”
Section: Approach‐ismentioning
confidence: 90%
“…Socio‐demographic data were collected by self‐reports and information on medical history was retrieved by chart reviews. Details on the methodology of APPROACH‐IS have been provided in a methods paper , and numerous papers have described findings obtained from this global sample or from patients from specific countries or regions .…”
Section: Approach‐ismentioning
confidence: 99%
See 2 more Smart Citations
“…However, any observed change is highly likely to be multifactorial. Having comorbidities or mental health issues may make a difference for example, as could age, gender, type of cancer, and socioeconomic status as well as time and type of intervention. Secondary aim of this study was therefore to identify potential predictors of (a) increased levels of concern at initial visit and (b) change in severity scores at reassessment.…”
Section: Introductionmentioning
confidence: 99%